PEMETAAN ZONA GEOMORFOLOGI DAN HABITAT BENTIK DI PULAU KOTOK BESAR MENGGUNAKAN KLASIFIKASI BERBASIS OBJEK - Ike Dori Candra; Vicentius P. Siregar; Syamsul B. Agus (Fakultas Perikanan dan Ilmu Kelautan, 2017)
This study used high-resolution satellite imagery of worldview-2 acquisition 5 October 2013. The purpose of this study was to explore the capability of high-resolution satellite imagery of worldview-2 to map the geomorphic zones of shallow water in Kotok Besar island. The method used is object-based image analysis. This method is able to define classes of objects based on spectral and spatial aspects. Image segmentation algorithm using multiresolution segmentation with different scala parameters for each level, level 1, level 2 and level 3. Shape and compactness are also customized for each level. Assign class at level 1 generates three classes, namely land, shallow water and deep water. Assign class at level 2 for geomorphic zone generates three class classes of reef flat, reef crest and reef slope. benthic habitat classification at level 3 produces 7 classes with an overall accuracy was 66.40%.